Business purpose in tax relations: regulatory and applied scientific analysis - Pilipenko, Aleksandr A. (Journal of the Belarusian State University. Law, 2019)
The theoretical and practical questions of a business purpose in tax relations are investigated. Based on the analysis, the author’s definition of a business purpose was developed, the need to work out criteria for distinguishing between legitimate and unlawful tax optimization was postulated, and proposals and directions for improving national legislation were determined.